Legal Liability of Fintech Operators for Personal Data Misuse in the Context of Unlawful Acts: Analysis of the Case of NS Versus AdaKami - Cen, Jesslyn Janet; Yulio, Pietro Grassio Eko; Gunawan, Theresia Aurellia; Gunawan, Telly (Dinasti Research, 2025)
The rapid development of financial technology (fintech) in Indonesia creates opportunities for financial inclusion while simultaneously raising concerns regarding consumer data protection. One prominent case is the dispute between NS and AdaKami, which demonstrates alleged misuse of personal data by debt collectors in debt collection practices. This research aims to analyze the fulfillment of the elements of tort (perbuatan melawan hukum/PMH) as stipulated in Article 1365 of the Indonesian Civil Code and to assess the scope of legal liability borne by fintech providers as data controllers. The study employs a normative juridical method with statutory and conceptual approaches, supported by a case study analysis. The findings indicate that all elements of PMH are fulfilled, including the existence of unlawful acts contrary to the Personal Data Protection Law (PDP Law), the Information and Electronic Transactions Law (ITE Law), and prevailing moral standards; the presence of fault in the form of intentional misconduct (dolus) by debt collectors and negligence (culpa in custodiendo) by AdaKami in supervising third parties; the occurrence of material and immaterial losses; and a causal relationship between the act and the harm suffered by the consumer. These findings affirm that fintech providers are not only contractually liable but also delictually liable through the application of strict liability in safeguarding personal data. Nevertheless, although the legal framework is already established through the Civil Code and the PDP Law, its implementation remains ineffective due to weak regulatory oversight and the heavy burden of proof imposed on consumers. Accordingly, this research underscores the necessity of strengthening consumer protection in fintech through strict liability enforcement, enhanced supervisory mechanisms, and the establishment of accessible and consumer-oriented dispute resolution systems